Advances in minimally invasive surgery in the treatment of colorectal cancer. Issue 1 (January 2008) - Brown, Carl J; Raval, Manoj J
Colorectal cancer (CRC) is the second leading cause of cancer-related death in the USA. Surgery is the primary treatment for most patients with CRC. Over the past 15 years, minimally invasive techniques for colorectal surgery have been developed. There is growing evidence that these techniques have significant advantages in short-term outcomes (e.g., postoperative pain and length of hospital stay) with similar long-term recurrence and overall survival. While transanal local excision has been shown to be inferior to radical resection for early rectal cancer, transanal endoscopic microsurgery (TEM) is a minimally invasive technique that appears to facilitate local excision in appropriate patients. TEM combined with radiotherapy has demonstrated promising early results and is currently being investigated in clinical trials as a potential alternative to radical surgery. We summarize the current literature on these minimally invasive approaches to CRC.